Interactive effects of adiposity and insulin resistance on the impaired lung function in asthmatic adults: cross-sectional analysis of NHANES data - Roham Sadeghimakki; Huw David McCarthy (Taylor & Francis Group, 2019)
Background: Obesity is considered a risk factor for both asthma and insulin resistance in adults. Insulin resistance (IR) also influences pulmonary function in the non-obese population. Aim: To investigate the modifying effect of insulin resistance on the predictive role of anthropometric measures in the estimation of impaired lung function among asthmatic adults. Subjects and methods: A cross-sectional study of 1276 adults extracted from the NHANES 2009-2012 database was performed. Adjusted multiple linear regression was conducted to analyse the contributory role of obesity and IR in predicting lung function among asthmatic adults. Results: BMI, waist circumference (WC) and waist-to-height ratio (WHtR) showed significantly negative correlations with FVC (r=-0.24, -0.18, -0.39, respectively; p < 0.001), FEV1(r=-0.24, -0.21, -0.40, respectively; p < 0.001) and FEF 25-75% (r=-0.15, -0.18, -0.27, respectively; p < 0.001). Even after adjustment for the covariates (age, gender, smoking history and standing height), BMI and HOMA-IR had significant relationships with FVC (β= −10.3; p < 0.01 and β= −16.0; p < 0.05) and FEV1 (β= −8.7; p < 0.01 and β= −11.7; p < 0.05). BMI could significantly predict the decreased FVC (β= −13.7; p < 0.01) and FEV1 (β= −10.7; p < 0.01) only in the insulin resistant asthmatics. Conclusion: WHtR and IR predict impaired lung function in overweight/obese asthmatic adults independently. IR also modifies the association between excessive adiposity and respiratory function in asthmatic adults.